GUIDELINES FOR DRIVING EDUCATIONAL SUSTAINABLE DEVELOPMENT GOAL OF PROVINCIAL EDUCATION OFFICE IN THE SOUTHERN ANDAMAN PROVINCIAL CLUSTER AREA - Kaewchumnong, Aunchisa; Yurarach, Subin (Journal of Education and Innovation, 2025)
This research is a policy-oriented aims to study: 1) to investigate the implementation of policies and participatory management in driving the sustainable development goals (SDGs) in education of the Provincial Education Office in the Southern Andaman provincial cluster area, and 2) to propose guidelines for driving the SDGs in education in the Southern Andaman provincial cluster area. The research uses a qualitative approach, based on the concept of policy implementation and participatory management theory as the research framework. The key informants consist of a total of six individuals. Research tools include two types: 1) reports on the progress of the SDGs in education and provincial education development plans, and 2) semi-structured interview which the data analysis was performed using content analysis. The research findings are as follows: 1) Regarding the implementation of policies, it involves linking them to the objectives and strategic issues in the provincial education development plan and carrying out projects/activities to promote and support the operation of all indicators. In terms of participatory management, it provides opportunities for personnel to be part of the SDG4 driving team, working together to think, share responsibility, and engage in actions to improve education quality in an inclusive, equitable manner, while supporting lifelong learning opportunities. 2) The guidelines for driving the SDGs in education are: (1) raising awareness and assigning responsibilities; (2) establish common goals for all relevant stakeholders involved in the area; (3) integrating and coordinating collaboration; (4) monitoring and evaluation progress for each indicator to facilitate review, adjustment, and further development; and (5) data collection and creation of a database for operations based on performance indicators.